Born to innovate? The birth‐order effect of CEOs on corporate innovation. (2nd August 2021) - Wan, Qing; Cheng, Xiaoke; Chan, Kam C.; Gao, Shenghao
Abstract: This study explores the effect of CEO birth order on corporate innovation. Using hand‐collected data, we find that firms led by firstborn CEOs are less innovative. This finding survives a number of robustness checks. When firms are more risky, non‐state‐owned or less financially constrained, the association between birth order and innovation is stronger, suggesting that the negative impact of firstborn CEOs is larger when their innovative personality is more demanding or influential. Meanwhile, firstborn CEOs have larger impact on corporate innovation when they are born in cities where Confucian culture are more influential or grow up in a low‐income family, consistent with our argument that sibling competition makes firstborns less innovative. Overall, our results suggest that firstborn CEOs have negative effect on corporate innovation because they are less innovative intrinsically.